If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + -3) + 5 = 4y + -3(x + y) Reorder the terms: 2(-3 + x) + 5 = 4y + -3(x + y) (-3 * 2 + x * 2) + 5 = 4y + -3(x + y) (-6 + 2x) + 5 = 4y + -3(x + y) Reorder the terms: -6 + 5 + 2x = 4y + -3(x + y) Combine like terms: -6 + 5 = -1 -1 + 2x = 4y + -3(x + y) -1 + 2x = 4y + (x * -3 + y * -3) -1 + 2x = 4y + (-3x + -3y) Reorder the terms: -1 + 2x = -3x + 4y + -3y Combine like terms: 4y + -3y = 1y -1 + 2x = -3x + 1y Solving -1 + 2x = -3x + 1y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. -1 + 2x + 3x = -3x + 3x + 1y Combine like terms: 2x + 3x = 5x -1 + 5x = -3x + 3x + 1y Combine like terms: -3x + 3x = 0 -1 + 5x = 0 + 1y -1 + 5x = 1y Add '1' to each side of the equation. -1 + 1 + 5x = 1 + 1y Combine like terms: -1 + 1 = 0 0 + 5x = 1 + 1y 5x = 1 + 1y Divide each side by '5'. x = 0.2 + 0.2y Simplifying x = 0.2 + 0.2y
| log(x)200=15 | | -4y^2-11y-8= | | -9m=27 | | 3(-(5u+1)-(-4u+3))=5(u+4) | | 4(-7x+13)=-144 | | s^2-4s-10=0 | | 4(-7+13)=-144 | | 5v-4=-14 | | 2(2x+3)=8x+3 | | 34234343423424342=2343242432425234123423424234r | | 28.3+m=15.25+16.3 | | 2=6+8 | | -3x^2+28x-21= | | .25m=2.25 | | 6.89+m=15.89 | | 7.25m=65.25 | | x^3-20*x^2+1000=0 | | 23+y=30 | | -1(2)(-2)= | | 6(3)+3(-2)= | | -6u^2+11u+20= | | 3-(-2)(5)= | | 6u^2-11u-20= | | 3+-2(5)= | | 10r^2-13r=-4 | | -26=-12u-9+7u | | 3-3(-1)= | | 11x-6=65 | | 7(-2)-3= | | 3a^2+5a+2=0 | | 9+2(-1)= | | 36-4x=16+6x |